Analisis Sentimen Pengguna Youtube Mengenai Analog Switch Off Menggunakan Word Embedding Dan Metode Long Short-Term - Mochamad Suhri Ainur Rifky; Amalia Anjani Arifiyanti; Reisa Permatasari (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
Analog Switch Off (ASO) or migration program from analog television to digital television is a program issued by the Ministry of Communication and Informatics in Indonesia. Some people provide different responses and opinions on YouTube comments about ASO. There are those who give positive or neutral comments. However, there were also those who gave negative comments. Sentiment analysis is a process that is carried out automatically in studying, retrieving, and processing textual data to obtain information and see responses or opinions about an issue or object towards positive, neutral or negative opinions. Thus sentiment analysis can be used as a reference in making organizational decisions, improving a service, or as a review of a product. Sentiment analysis was performed using word embedding with Word2Vec, and sentiment classification using the Long Short-Term Memory (LSTM) method. The results of the evaluation test are 92% accuracy, 92% precision, 92% recall, and 92% f1-score.